Strategi Kreatif Fremantle Indonesia Dalam Memastikan Program Family 100 Tetap Diminati - Adinda Regita Sutanti; Feri Ferdinan Alamsyah; Sabila Adinda Puri Andarini (UNIVERSITAS PAKUAN, 2024)
This study aims to illustrate how Fremantle Indonesia's creative strategy in ensuring the Family 100 program remains in demand. This research uses the concept of 13 elements of creative strategy in event production according to Naratama consisting of the target audience, script language, event format, punch line, gimmick and fanfare, clip hanger, tune and bumper, artistic director, music and fashion, rhythm and rhythm of the show, logo and music track, general rehearsal and interactive program. This research uses qualitative methods with a type of case study research. The research was conducted at the Fremantle Indonesia office. The data collection techniques used are interviews, observations, and documentation. The triangulation used in this study is source triangulation. The results of this study show that the Family 100 program applies 13 elements of creative strategy in event production according to Naratama, but the Family 100 program also has a focus that becomes the main strategy, namely with gimmicks through